The effect of patient anxiety and depression on motion during myocardial perfusion SPECT imaging. Issue 1 (December 2016) - Lyra, Vassiliki; Kallergi, Maria; Rizos, Emmanouil; Lamprakopoulos, Georgios; Chatziioannou, Sofia
Abstract Background Patient motion during myocardial perfusion SPECT imaging (MPI) may be triggered by a patient's physical and/or psychological discomfort. The aim of this study was to investigate the impact of state anxiety (patient's reaction to exam-related stress), trait anxiety (patient's personality characteristic) and depression on patient motion during MPI. Methods All patients that underwent MPI in our department in a six-month period were prospectively enrolled. One hundred eighty-three patients (45 females; 138 males) filled in the State-Trait Anxiety Inventory (STAI) and the Beck Depression Inventory (BDI), along with a short questionnaire regarding their age, height and weight, level of education in years, occupation, and marital status. Cardiovascular and other co-morbidity factors were also evaluated. Through inspection of raw data on cinematic display, the presence or absence of patient motion was registered and classified into mild, moderate and severe, for both phases involved in image acquisition. Results The correlation of patient motion in the stress and delay phases of MPI and each of the other variables was investigated and the corresponding Pearson's coefficients of association were calculated. The anxiety-motion(r = 0.43, P < 0.0001) and depression-motion(r = 0.32, P < 0.0001) correlation results were moderately strong and statistically significant for the female but not the male patients. All the other variables did not demonstrate any association with motion in MPI, except a weak correlation between age and motion in females(r = 0.23, P < 0.001) . Conclusions The relationship between anxiety-motion and depression-motion identified in female patients represents the first supporting evidence of psychological discomfort as predisposing factor for patient motion during MPI.